2006
DOI: 10.1016/j.ydbio.2006.08.007
|View full text |Cite
|
Sign up to set email alerts
|

A genomic view of the sea urchin nervous system

Abstract: The sequencing of the Strongylocentrotus purpuratus genome provides a unique opportunity to investigate the function and evolution of neural genes. The neurobiology of sea urchins is of particular interest because they have a close phylogenetic relationship with chordates, yet a distinctive pentaradiate body plan and unusual neural organization. Orthologues of transcription factors that regulate neurogenesis in other animals have been identified and several are expressed in neurogenic domains before gastrulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
282
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(300 citation statements)
references
References 186 publications
17
282
0
1
Order By: Relevance
“…Note the presence of the pigment cells, probably containing opsin, in and around the ossicles (figure 2g). Nerves are also present along the entire length of the tube foot under the epithelium, forming a nerve plexus (figure 2h) that terminates in a ganglion at the distal portion of the tube foot as previously described for sea urchins [30][31][32]. Using primers specific for opsins, a 1.563 Kbp cDNA was amplified from the green sea urchin tube foot.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note the presence of the pigment cells, probably containing opsin, in and around the ossicles (figure 2g). Nerves are also present along the entire length of the tube foot under the epithelium, forming a nerve plexus (figure 2h) that terminates in a ganglion at the distal portion of the tube foot as previously described for sea urchins [30][31][32]. Using primers specific for opsins, a 1.563 Kbp cDNA was amplified from the green sea urchin tube foot.…”
Section: Resultsmentioning
confidence: 99%
“…First described in Xenopus, melanopsin is now known to confer photosensitivity on non-photosensitive cells types [50,51]. It has been hypothesized that melanopsin sets the circadian clock through non-ocular light detection [52], and is also expressed in sea urchins [30]. Additionally, an encephalopsin homologue has been sequenced from sea urchins [30,41], which is expressed at the tips of the larval arms of plutei and tube feet of adults [16,41], and potentially aids in the detection of light by planktonic larvae vertically migrating in the water column.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, six different opsins plus other essential components of the signal transduction cascade of photoreceptor cells (PRCs) were identified (10,11). RT-PCR showed that many of the discovered genes are expressed in adult S. purpuratus tube feet (10,11), suggesting the presence of a more elaborate light-sensing apparatus than was previously assumed.…”
mentioning
confidence: 91%
“…The genome sequencing of the purple sea urchin Strongylocentrotus purpuratus led to the surprising discovery of a large number of typical "eye" genes, like pax6, atonal, neuroD, and barh1, which in vertebrates pattern early retina development (10). Moreover, six different opsins plus other essential components of the signal transduction cascade of photoreceptor cells (PRCs) were identified (10,11).…”
mentioning
confidence: 99%